The Effect of One Circuit Training Session on the Serum Levels of Brain-Derived Neurotrophic Factor and Insulin-Like Growth Factor-1 in the Elderly - Vahid Valipour Dehnou; Reza Motamedi (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Physical activity is effective in improving cognitive function in older adults. Such function may be mediated by the upregulation of neurotrophic growth factors like Brain-Derived Neurotrophic Factor (BDNF) and Insulin-like Growth Factor-1 (IGF-1). The present study aimed to assess and compare the effect of 1 session of circuit training on the serum levels of BDNF and IGF-1 in elderly males and females. Methods & Materials This quasi-experimental study was carried out in Khorramabad City, Iran in 2017. Five men (Mean±SD age=64.40±6.69 years, Mean±SD weight=74.8±5.63 kg, Mean±SD height=174.4±4.16 cm), and 5 women (Mean±SD age=64.5±60.55 years, Mean±SD weight=65±5.43 kg, Mean±SD height=167±5.Micipated voluntarily in this study. Three days before performing the training protocol, all subjects became familiarized with the methods of performing exercises at their homes. On the training day, at first, their blood samples were obtained; then, the subjects performed circuit training for approximately 1 hour. Second blood samples were obtained 3 minutes after the training session. The Paired sample t test and analysis of covariance were used to identify any significant differences. The statistical significance level was set at P<0.05. Results This study was carried out on 10 elderly males and females. Results suggested that the serum concentration of BDNF (P<0.05) significantly increased and IGF-1 (P<0.05) significantly decreased. However, the differences between males and females in BDNF (P>0.05) and IGF-1 (P>0.05) were not significant. However, the percent changes of BDNF (22.78 vs. 27.91) and IGF-1 (-10.55 vs. -12.37) were lower in males than females. Conclusion Circuit training for approximately 1 hour increases the serum concentration of BDNF and decreases IGF-1 in elderly males and females. Therefore, it is recommended that a body weight circuit training be performed in elderly males and females to improve their cognitive status.